„The Age of Disguise” in Peter Ackroyd’s Historical Novels - Lipski, Jakub (Porównania, 2016)
Peter Ackroyd’s literary output is characterised by a clear interrelationship between fiction and popular historiography. This is best manifested in his unwavering interest in the form of the historical novel. The present article is devoted to the three novels which creatively reconstruct selected events of the eighteenth century: Hawksmoor (1985), Chatterton (1987) and The Lambs of London (2004). It is argued that the recurrent themes, characters and ideas result from Ackroyd’s understanding of the century as “the Age of Disguise”. The metaphor of disguise accurately renders the specificity of the time when the Delphic precept “know then thyself” was taking on a new dimension. Informed by New Historicism and the theory of the postmodern historical novel, the following article demonstrates that Ackroyd’s vision of the eighteenth century corresponds with this approach to the period.